A Unique Combination of Aerodynamic and Surface Properties Contribute to Surface Cooling in Restored Wetlands of the Sacramento‐San Joaquin Delta, California. Issue 7 (10th July 2018) - Hemes, Kyle S.; Eichelmann, Elke; Chamberlain, Samuel D.; Knox, Sara H.; Oikawa, Patricia Y.; Sturtevant, Cove; Verfaillie, Joseph; Szutu, Daphne; Baldocchi, Dennis D.
Abstract: Land use change and management affect climate by altering both the biogeochemical and biophysical interactions between the land and atmosphere. Whereas climate policy often emphasizes the biogeochemical impact of land use change, biophysical impacts, including changes in reflectance, energy partitioning among sensible and latent heat exchange, and surface roughness, can attenuate or enhance biogeochemical effects at local to regional scales. This study analyzes 3 years (2015–2017) of turbulent flux and meteorological data across three contrasting wetland restoration sites and one agricultural site, colocated in the Sacramento‐San Joaquin Delta, California, USA, to understand if the biophysical impacts of freshwater wetland restoration can be expected to attenuate or enhance the potential biogeochemical benefits. We show that despite absorbing more net radiation, restored wetlands have the potential to cool daytime surface temperature by up to 5.1 °C, as compared to a dominant drained agricultural land use. Wetland canopy structure largely determines the magnitude of surface temperature cooling, with wetlands that contain areas of open water leading to enhanced nighttime latent heat flux and reduced diurnal temperate range. Daytime surface cooling could be important in ameliorating physiological stress associated with hotter and drier conditions and could also promote boundary layer feedbacks at the local to regional scale. With a renewed focus on the mitigation and adaptation potential of natural and working lands, we must better understand the role of biophysical changes, especially in novel land use transitions like wetland restoration. Plain Language Summary: Land use change and management affect climate by altering both the cycling of greenhouse gases and how energy and water are exchanged between the ecosystem and the atmosphere. These energy and water impacts can have local to regional implications on surface and air temperature. This study analyzes 3 years (2015–2017) of measured water and energy exchange at three contrasting wetland restoration sites and one agricultural site, all located in the Sacramento‐San Joaquin Delta, California, USA. Restoring drained agricultural fields to flooded wetlands causes a rougher canopy, with more exposed water, and alters the energy partitioning. This results in growing season and daytime surface cooling, which could enhance the other benefits of wetland restoration, like soil buildup, habitat creation, and carbon sequestration. Land use policies should consider both the greenhouse gas and the energy and water implications of the promoted land use change to fully account for the climatic impact. Key Points: We found significant surface temperature differences over drained agricultural peatland and restored wetlands Restored wetlands' tall, emergent canopy structure delays heat exchange with the atmosphere, causing a daytime and growing season cooling effect Land use policy must consider biophysical impacts in addition to biogeochemical benefits, especially in novel land use transitions